2015
DOI: 10.1213/ane.0000000000000757
|View full text |Cite
|
Sign up to set email alerts
|

The RECITE Study

Abstract: Residual paralysis is common at tracheal extubation and PACU arrival, despite qualitative neuromuscular monitoring and the use of neostigmine. More effective detection and management of NMB is needed to reduce the risks associated with residual NMB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(26 citation statements)
references
References 30 publications
0
25
0
1
Order By: Relevance
“…The prevalence of residual neuromuscular blockade was 22.0% in our cohort of patients who received low dose atracurium (<2xED 95 ). Other studies on full intubating dose (>2xED 95 ) of atracurium with ETT showed prevalence ranging from 32-64.6% [17][18][19].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The prevalence of residual neuromuscular blockade was 22.0% in our cohort of patients who received low dose atracurium (<2xED 95 ). Other studies on full intubating dose (>2xED 95 ) of atracurium with ETT showed prevalence ranging from 32-64.6% [17][18][19].…”
Section: Discussionmentioning
confidence: 92%
“…Despite the use of atracurium, a sizable proportion of patients (85 out of 109, 78.0%) were not reversed. The RECITE trial also shows a startling rNMB prevalence of 64.6% even among patients who were reversed with neostigmine [18]. None of the patients in our study population were assessed via peripheral nerve stimulator to accurately assess the ToF at the end of the surgery to guide usage of neostigmine.…”
Section: Discussionmentioning
confidence: 94%
“…[7,9,18] In the majority of cases, a single dose of NMB was administered. This may have been related to the duration of most anesthesia (approximately 2 hours), a result similar to those described in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…[2,57] Furthermore, the low use of neuromuscular monitoring and undesired effects of inadequate neostigmine doses have sparked a discussion on the use or nonuse of reversal agents. [8] Thus, the study of the use of NMB and their reversal agents is mandatory in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] Residual paralysis is common at the time of tracheal extubation and arrival at the post-anaesthetic care unit, despite qualitative neuromuscular monitoring and use of neostigmine. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%